Takis Würger’sNovel Stella (2019)—Holocaust Literature of aNew Generation? - Ohme, Andreas (Poznańskie Studia Slawistyczne, 2023)
Takis Würger’s novel Stella, published in 2019, has received mostly unenthusiastic reviews from literary critics because, in their opinion, it does not do justice to Stella Goldschlag's historical persona. Rather, the text merely turns a tragic conflict into Holocaust kitsch. In order to examine this judgement, the article analyses the poetics of the novel. This analysis reveals two things: the text does not in fact strive for a historically accurate portrayal of Stella Goldschlag, but reflects on the different ways of accessing the historical phenomenon. In this sense, Stella may be seen as an passable attempt to write modern literature about the Holocaust for today's generation. It does not, however, do so consistently because it oscillates between the genre of the historical novel and allegory. The fictitious narrator, Friedrich, also proves inconsistent. His mixture of naivety and pathos indeed tends towards kitsch.